COVID-19 and the mass incarceration of Indigenous peoples - King, Paula; Cormack, Donna; Keenan, Rawiri (Journal of Indigenous Social Development, 2020)
Similar to experiences of Indigenous peoples globally, Māori in the nation-state known as New Zealand (NZ) have been subjected to mass incarceration by the colonial state. Places of detention are dangerous environments for the spread of COVID-19. We are deeply concerned about the potential for disproportionate impacts of COVID-19 on Māori and other Indigenous peoples within these environments as many have health conditions and/or multiple comorbidities compounding the risks of severe illness and death from COVID-19. We call for the NZ government to honour te Tiriti o Waitangi obligations and uphold Indigenous rights contained within the United Nations Declaration on the Rights of Indigenous Peoples and other international rights instruments. A whole-of-government commitment to an equitable public health approach is required to: 1) rapidly reduce the numbers of Māori in sites of detention; 2) implement effective, timely, evidenced informed measures to reduce the risk of COVID-19, in line with World Health Organization recommendations; 3) prevent the torture and cruel, inhuman or degrading treatment or punishment of detained Māori during COVID-19; and, 4) eliminate double-celling. Although focused on NZ, the themes we highlight are likely of relevance for Indigenous peoples across the globe in our collective resistance to the COVID-19 pandemic.
Keywords: UNDRIP; covid-19; incarceration; racism; tiriti o waitangi/treaty of waitangi; treaty obligations

Seeing the unseen: evidence of kaupapa Māori health interventions - Rolleston, Anna K; Cassim, Shemana; Kidd, Jacquie; Lawrenson, Ross; Keenan, Rawiri; Hokowhitu, Brendan (AlterNative: An International Journal of Indigenous Peoples, 2020)
M?ori in Aotearoa have higher incidence, prevalence and mortality from chronic disease. The dominant narrative in Aotearoa about the reasons for M?ori ill health neglects to acknowledge the history of colonisation and failures of the health system, alongside the holistic view of health taken by M?ori focusing on collective, wh?nau-based outcomes. In this article, we review health interventions for chronic disease that have a kaupapa M?ori philosophical basis. Our findings demonstrate that there is no clear process in health service design, delivery, research and funding that values and understands m?tauranga M?ori. Western knowledge systems are inadequate for collecting and presenting M?ori knowledge. Overall, we highlight that the tension between acknowledging that a ?by M?ori, for M?ori? approach is best, and the difficulty in defining appropriate evidence collection methodology and outcome measures when funders and policy makers continue to require Western-centric interventions is an obstacle to improving M?ori health outcomes.
Keywords: health; health equity; kaupapa māori

Hā Ora: Reflecting on a Kaupapa Māori community engaged co-design approach to lung cancer research - Kidd, Jacquie; Cassim, Shemana; Rolleston, Anna; Keenan, Rawiri; Lawrenson, Ross; Sheridan, Nicolette; Warbrick, Isaac; Ngaheu, Janette; Hokowhitu, Brendan (2021)
Co-designed research is gaining prominence within the health care space. Community engagement is a key premise of co-design and is also particularly vital when carrying out kaupapa Māori research. Kaupapa Māori describes a “by Māori, for Māori” approach to research in Aotearoa/New Zealand. This article discusses the research process of Hā Ora: a co-design project underpinned by a kaupapa Māori approach. The objective was to explore the barriers to early presentation and diagnosis of lung cancer, barriers identified by Māori. The team worked with four rural Māori communities, with whom we aimed to co-design local interventions that would promote earlier diagnosis of lung cancer. This article highlights and unpacks the complexities of carrying out community- engaged co-design with Māori who live in rural communities. In particular, we draw attention to the importance of flexibility and adaptability in the research process. We highlight issues pertaining to timelines and budgets, and also the intricacies of involving co-governance and advisory groups. Overall, through this article, we argue that health researchers need to prioritise working with and for participants, rather than on them, especially when working with Māori communities.
Keywords: co-governance; health inequity; kaupapa māori; research